PERAN OPERATOR LIVE STREAMING DALAM MENDUKUNG AKTIVITAS DIGITAL MARKETING DI PT BORWITA INDAH ORBIZ - Fayyaz Ahsan Widyanto; Amiruddin Saleh (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The rapid evolution of digital marketing through live streaming platforms has shifted consumer behavior toward interactive shopping experiences. While the success of live commerce is often attributed to the host's on-screen performance, it fundamentally relies on backend technical operational stability to achieve optimal sales targets. Therefore, this study aims to discover and describe the role of the live streaming operator in supporting digital marketing activities at PT Borwita Indah ORBIZ, as well as to analyze the operator's contribution in maintaining production quality and broadcast continuity as an integral part of the company's marketing communication. The research method employed is a descriptive qualitative approach utilizing a case study design. Data collection was conducted through active participatory observation—where the researcher directly acted as the operator—and systematic documentation of the operational broadcasting procedures. The results demonstrate that the operator plays a highly crucial role in integrating broadcasting software (OBS Studio) with the company's operational hardware, including cameras and wireless microphones. Furthermore, the operator's capability to execute rapid and effective troubleshooting against unpredictable technical constraints—such as internet network instability, audio leaks, camera overheating, and software crashes—serves as the determining factor in sustaining broadcast stability. Ultimately, this technical readiness and swift problem-solving significantly enhance audience retention, ensure interactive communication comfort, and provide an optimal environment for the host to encourage sales conversions, thereby successfully supporting the company's overall digital marketing strategy.